Detection of neurological damage during open-heart surgery. Issue 4 (July 1973) - Branthwaite, M. A.
Abstract : Branthwaite, M. A. (1973). Thorax, 28, 464-472. Detection of neurological damage during open-heart surgery. Cerebral activity during open-heart surgery has been recorded in 140 patients using a heavily filtered electroencephalograph, the Cerebral Function Monitor (CFM). Unlike the conventional electroencephalogram the CFM record is recorded at slow speeds, is filtered to minimize electrical interference, and is easy to interpret. A high incidence (62·9%) of alteration in electrical activity was noted at the onset of perfusion, and several different patterns of change are described. Ten patients suffered neurological damage to a degree which produced physical signs in the postoperative period. In eight of these 10 cases, abnormal depression of the CFM record was noted during perfusion; the depression occurred at the onset on five occasions. Equivocal changes were noted at the onset of perfusion in one patient whose neurological lesion may have been related to a postoperative cardiac rhythm disorder. One patient sustained a midbrain lesion, probably at the onset of perfusion, and the CFM record during operation was unremarkable. The incidence of both neurological damage and depression of the CFM record at the onset of perfusion has decreased since filters for microemboli have been included in the perfusion circuit. It is concluded that the CFM is a useful means of detecting acute changes in cortical activity during open-heart surgery. The risk of cerebral damage is high at the onset of perfusion when both hypotension and microemboli from the extracorporeal circuit may contribute to the neurological lesion.